WAYS TO INCREASE THE EFFECTIVENESS OF THE ACTIVITY OF THE KOKAN STATE PEDAGOGICAL INSTITUTE BASED ON THE 3.0 MODEL IN HIGHER EDUCATION - Madaminova Husnida Rashidovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article, based on the 3.0 model in higher education, there is an opinion about ways to improve the effectiveness of the Kokan State Pedagogical Institute